Repurposing of propane oxidative-dehydrogenation catalysts to deoxygenation of vegetable oils for green diesel production - S. Lucantonio; G. Di Vito Nolfi; C. Courson; K. Gallucci; A. Di Giuliano; L. Rossi (Fuel Processing Technology)
The market for diesel fuel will grow in the next years. Green diesel – alkanes produced through deoxygenation (DO) with H2 of triglyceride-based biomasses – can help cover this demand sustainably. Repurposing non-noble-metals catalysts is a faster affordable route to spread DO at larger scales. NiCoMo and ZnCoMo catalysts were previously proposed in the literature for oxidative-dehydrogenation of propane and unprecedentedly repurposed for DO in this work. DO tests on NiCoMo and ZnCoMo were performed according to an unreplicated 23 factorial Design of Experiment (DoE) with three replications at center point. Temperature (T), catalyst-to-oil ratio (γ), DO duration (t) were the design-factors, at levels: 280–320 °C; 4–10 %w/w; 2–6 h. Both catalysts performed promisingly(NiCoMo and ZnCoMo best conversion of 100 %, NiCoMo and ZnCoMo best diesel yields of 73 % and 68 %, respectively). Analysis of Variance was performed on main effects and factor interactions of all measured quantities and performance parameters, obtaining surface responses equations. Additionally, NiCoMo and ZnCoMo underwent recycling tests (four DO cycles) to evaluate reusability at 320 °C-10 %w/w-2 h: catalysts ensured for four cycles stable 100 % conversion of triglycerides and slightly growing diesel yield (NiCoMo: 67 % to 72 %; ZnCoMo: 64 % to 74 %). Overall, the selected dehydrogenation catalysts were successfully repurposed for DO at laboratory-scale. Although further evaluations should be performed for a balanced perspective regarding the industrial potential and sustainability of DO by repurposed NiCoMo and ZnCoMo (e.g., catalyst synthesis scalability, switch from batch to continuous production), the ease (cost-effectiveness) of the catalytic synthesis and process performances seem promising for their scalability.